(untitled) (Kronika Bydgoska, 2021)
The article describes the profile and brief career of Jan Maciaszek, the first Polish mayor of Bydgoszcz in the Second Republic of Poland. His short term lasted between January 19, 1920 and September 5, 1921. This devoted patriot and activist fighting for the independence of Poland, holding many public functions, fell victim to the anti-German manifestations and direct riots provoked by the Bydgoszcz division of the National Workers’ Party. He resigned from his post and stayed in Bydgoszcz, where he was running a well-known law firm.